Balloon Test Occlusion of Internal Carotid Artery in Recurrent Nasopharyngeal Carcinoma Before Endoscopic Nasopharyngectomy: A Single Center Experience - Yang, Renhao; Wu, Hui; Chen, Binghong; Sun, Wenhua; Hu, Xiang; Wang, Tianwei; Guo, Yubin; Qiu, Yongming; Dai, Jiong (Frontiers in Oncology, 2021)
Objectives: Endoscopic nasopharyngectomy(ENPG) is a promising way in treating recurrent nasopharyngeal carcinoma(rNPC), but sometimes may require therapeutic internal carotid artery(ICA) occlusion beforehand. Balloon test occlusion (BTO) is performed to evaluate ischemic tolerance for ICA sacrifice. However, absence of neurological deficits during BTO does not preclude occur of delayed cerebral ischemia after permanent occlusion. In this study, we evaluate the utility of near-infrared spectroscopy (NIRS) regional cerebral oxygen saturation(rSO2) monitoring and during BTO to quantify ischemic tolerance and to identify the valid cut-off values for safe carotid artery occlusion and to reveal some angiographic findings of collateral flow that helps to predict BTO results. Material and Methods: 87 BTO of ICA were performed from November 2018 to November 2020 at authors’ institution. 70 of 87 angiographies collateral flow were performed in time during BTO and classified into several Subgroups and Types according to their collateral flow configurations. 62 of 87 cases accepted monitoring of cerebral rSO2. Categorical variables were compared by using Fisher exact tests and Mann–Whitney U tests. Receiver operating characteristic curve analysis was used to determine the most suitable cut-off value. Results: The most suitable cut-off △rSO2 value for detecting BTO-positive group obtained through ROC curve analysis was 5%(sensitivity: 100%, speciﬁcity: 86%).NIRS rSO2 monitoring wasn’t able to detect BTO false-negative results(p=0.310). The anterior Circle was functionally much more important than the posterior Circle among the primary collateral pathway. The presence of secondary collateral pathways was considered as a sign of deteriorated hemodynamic condition of the brain during BTO. In Type5 and Type6, reverse blood flow to the ICA during BTO protected patients from delayed cerebral ischemia after therapeutic ICA occlusion(p=0.0357). In SubgroupIV, absence of the posterior Circle was significantly associated with BTO-positive results(P=0.046). Conclusion: CTA/MRA scanning of the brain and Matas or Allcock maneuvers are essential before BTO. Angiographic findings before and during BTO could predict some of the BTO results. Angiographic BTO can be performed with NIRS cerebral oximeter for its correct prediction of most rSO2 outcome of ICA sacrifice. However, different adjunctive techniques should be elected according to the hemodynamic changes in cerebral arteries during BTO.